Pediatric weight bias in prehealth profession undergraduates: an idiographic approach. Issue 1 (17th October 2019) - Basch, Molly C; Mayer-Brown, Sarah; Robinson, Michael E; Janicke, David M
Abstract : A substantial proportion of pre-health profession undergraduate students relied on cues of pediatric patient and mother weight status (healthy weight or obese) when making assessments about anticipated treatment adherence and responsibility for health. Abstract: Bias toward individuals with overweight/obesity (OV/OB) exists among health professionals and trainees with the potential to affect the quality of healthcare interactions. Given most research is adult-focused, this study aimed to examine the influence of weight status on clinical judgments in a pediatric context. Sixteen virtual human scenes representing hypothetical medical encounters of pediatric patients and their mothers were presented to prehealth profession undergraduates ( n = 92). Characteristics, or cues, of patient and mother weight status (healthy weight vs. obese) and dyad race (Caucasian vs. African American) were manipulated across scenes. Participants provided ratings for assessment questions, including perceived treatment adherence and responsibility for health, for each scene. Data were examined via idiographic (i.e., individual-level) analysis, which involved generation of separate multiple regressions per participant per assessment question to capture the influence of the cues on participants' ratings. Results represent secondary outcomes from another study published elsewhere. Current analyses revealed that 12%–22% of participants relied on cues of weight status when making assessments about patient and mother adherence and responsibility for health. The majority of these participants equated higher weight status with poorer anticipated treatment adherence and greater health responsibility. Results suggest that the weight status of pediatric patients and their mothers' plays a considerable role in prehealth profession undergraduates' clinical judgments, with the future potential to affect disparities in pediatric care. This study highlights the importance of considering child and maternal factors and utilizing a novel approach that may serve as a model for further investigation of this issue.